ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMP PADA MATERI HIMPUNAN: STUDY KASUS DI SMP NEGERI 1 CIBADAK - Yuyun Rahayu; Heni Pujiastuti (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2018)
This research is a type of descriptive research that aims to describe the ability to understand students' mathematical concepts in solving problems, especially related to the concept of set. The subjects of this study were seventh grade students of SMP Negeri 1 Cibadak Lebak Regency 2018/2019 Academic Year as many as 30 people. The instrument used in this study is a test of mathematical comprehension ability in the form of description. The data obtained were analyzed descriptively to find out the mean, mode, percentage of ideal scores, standard deviations and variances. In addition, it also describes the ability of students' mathematical understanding for each indicator. The results of the analysis are obtained: 1) Overall the average ability of students' mathematical understanding is 70% of the ideal score; 2) The average mathematical ability of students on indicator 1 is 56% of the ideal score; 3) The average ability of students on indicator 2 is 88%; 4) The average mathematical ability of students on indicator 3 is 79% of the ideal score; 5) The average mathematical ability of students on indicator 4 is 54% of the ideal score; 6) The average mathematical ability of students on indicator 5 is 84% ​​of the ideal score. The ability of students' mathematical understanding based on the average of each indicator, the lowest is the fourth indicator, namely the ability to present the concept. And the highest average is the second indicator, namely the ability to identify examples and not examples because the questions given are counted easily. Included in the category of very high mathematical understanding ability there are 7 people, 11 people high, 8 people enough, and 4 people low. Overall students who are able to understand mathematically 18 people who get a score above KBM (Minimum Learning Criteria) of 30 students.